Stress as a Chromatin Landscape Architect - Vertii, Anastassiia (Frontiers in Cell and Developmental Biology, 2021)
The exponential development of methods investigating different levels of spatial genome organization leads to the appreciation of the chromatin landscape's contribution to gene regulation and cell fate. Multiple levels of 3D chromatin organization include chromatin loops and topologically associated domains, followed by euchromatin and heterochromatin compartments, chromatin domains associated with nuclear bodies, and culminate with the chromosome territories. 3D chromatin architecture is exposed to multiple factors such as cell division and stresses, including but not limited to mechanical, inflammatory, and environmental challenges. How exactly the stress exposure shapes the chromatin landscape is a new and intriguing area of research. In this mini-review, the developments that motivate the exploration of this field are discussed.